Prezydia wojewódzkich rad narodowych jako instancje odwoławcze od orzeczeń karno-administracyjnych w latach 1951–1958 na przykładzie Prezydium Wojewódzkiej Rady Narodowej w Zielonej Górze - Halczak, Bohdan (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
In 1951, the communist authorities introduced the institution of a penal college in Poland. This institution was modeled on the legislation in force in the Union of Soviet Socialist Republics. Colleges were not courts but performed judicial functions. The fi nal instance of appeal against the rulings of the colleges was the Presidium of the Provincial National Council. The article showed that a large part of the rulings issued by colleges in the Zielona Góra region in the years 1951–1957 were annulled by the Presidium. College rulings were often in confl ict with applicable law.
Keywords: Polska; komunizm; kolegia karne; województwo zielonogórskie